INNOVATIVE CONTEMPORARY APPROACHES TO PERIODONTITIS TREATMENT - Sunnatov Davron Xusniddin o’g’li; Khatamov Ulug'bek Altibayevich (Western European Studies, 2025)
This article analyzes modern, innovative, and minimally invasive methods used in the treatment of periodontitis. In addition to traditional mechanical and pharmacological treatment methods, contemporary dental practice is increasingly incorporating techniques such as laser therapy, PRF (Platelet-Rich Fibrin), photodynamic therapy, ozone therapy, biomodulators, and probiotics. These methods offer advantages such as reducing inflammation, ensuring pain relief, promoting rapid tissue regeneration, and effectively eliminating infections.
Keywords: Periodontics; Laser Therapy; PRF